2015
DOI: 10.5194/acp-15-8831-2015
|View full text |Cite
|
Sign up to set email alerts
|

New fire diurnal cycle characterizations to improve fire radiative energy assessments made from MODIS observations

Abstract: Abstract. Accurate near real time fire emissions estimates are required for air quality forecasts. To date, most approaches are based on satellite-derived estimates of fire radiative power (FRP), which can be converted to fire radiative energy (FRE) which is directly related to fire emissions. Uncertainties in these FRE estimates are often substantial. This is for a large part because the most often used low-Earth orbit satellite-based instruments such as the Moderate Resolution Imaging Spectroradiometer (MODI… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
74
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(80 citation statements)
references
References 49 publications
4
74
0
2
Order By: Relevance
“…This includes on-going developments of GFAS which aim at providing emission estimates with an hourly temporal resolution by combining FRP observations from both polar orbiting and geostationary satellites. Key pre-requisites are the implementation of a model for the diurnal cycle of FRP (Andela et al, 2015) and a suitable bias correction for geostationary FRP products to account for the omission of low intensity fires, building on the simple linear bias corrections applied currently in the FRP-GRID products.…”
Section: Discussionmentioning
confidence: 99%
“…This includes on-going developments of GFAS which aim at providing emission estimates with an hourly temporal resolution by combining FRP observations from both polar orbiting and geostationary satellites. Key pre-requisites are the implementation of a model for the diurnal cycle of FRP (Andela et al, 2015) and a suitable bias correction for geostationary FRP products to account for the omission of low intensity fires, building on the simple linear bias corrections applied currently in the FRP-GRID products.…”
Section: Discussionmentioning
confidence: 99%
“…This means that the resulting product is more representative of the diurnal maximum of fire intensity. The rationale behind this choice is that several studies showed that most emissions from biomass burning occur within a few hours of a peak time, typically during the early afternoon (Andela et al, 2015;Freeborn et al, 2009Freeborn et al, , 2011Roberts et al, 2009). The daily gridded fields of the four injection height parameters are then assimilated alongside FRP in the data assimilation step of GFAS.…”
Section: Integration Of the Injection Height Algorithms Into Gfasmentioning
confidence: 99%
“…Wang et al (2006) claimed that the application of hourly emission data is crucial for a realistic dispersion of the smoke near the source region. With geostationary satellites, it is possible to characterize the diurnal cycle of the fires (Kaiser et al, 2009b;Andela et al, 2015). Zhang and Kondragunta (2008) analyzed the daily variability by considering variations of the fire pixel size.…”
Section: Diurnal Cyclementioning
confidence: 99%